Ibn Taymiyyah’s Theological Approach Illustrated: On the Essence (Dhat) and Attribites (Sifat) of Allah - Siraje Abdallah, Ssekamanya (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Ibn Taymiyyah’s Theological Approach Illustrated: On the Essence (Dhat) and Attribites (Sifat) of Allah